Challenges in Implementing Digital Technology to Enhance Public Administration Efficiency in a Metropolitan City - Ahmadzai, Zahra; Rayi, Imam; Mirwais, Lodhi (Journal Social Civilecial, 2023)
This study examines the challenges of implementing digital technology to enhance the efficiency of public administration services in a metropolitan city. With the growing demand for digital transformation in public services, this research focuses on identifying key obstacles and understanding their impact on the adoption process. Through qualitative methods, including in-depth interviews with public administration employees and citizens, the study explores factors such as infrastructure readiness, cybersecurity concerns, resistance to change, technological inequality, and interoperability issues. Findings reveal that while infrastructure preparedness and technological literacy are fundamental to the successful integration of digital systems, cybersecurity risks and resistance to change remain significant barriers. Additionally, technological inequality exacerbates the digital divide, making access to digital services unequal, particularly among marginalized communities. The research also highlights the challenges related to system interoperability and the alignment of policies across public sector organizations. These findings contribute to the existing body of literature by providing a deeper understanding of the specific contextual factors influencing digital governance in metropolitan settings. The study concludes by offering recommendations for overcoming these challenges, emphasizing the need for comprehensive strategies that address both technical and social dimensions of digital transformation.